2011
DOI: 10.4067/s0034-98872011000700010
|View full text |Cite
|
Sign up to set email alerts
|

Screen viewing, body mass index, cigarette smoking and sleep duration in Belgrade University student population: results of an observational, cross-sectional study

Abstract: Background (Rev Med Chile 2010; 139: 896-901).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
1
0
2
Order By: Relevance
“…The same conclusion was reached by the remaining forty-two studies involving children and adolescents, as well as a study conducted on European adolescents from eight countries, which found that consumption of salty snacks and sugary drinks were higher in groups that did not meet physical activity and sedentary screen time recommendations 24 . In more recent studies, another important factor associated with screen time is smoking habit, with smokers spending more time watching TV 25 . Conversely, smokers appear to spend more time in front of a screen with smoking cessation influencing this association by reducing screen time 26 .…”
Section: Screen Time For Work (First Row) or Entertainment (Second Ro...mentioning
confidence: 99%
“…The same conclusion was reached by the remaining forty-two studies involving children and adolescents, as well as a study conducted on European adolescents from eight countries, which found that consumption of salty snacks and sugary drinks were higher in groups that did not meet physical activity and sedentary screen time recommendations 24 . In more recent studies, another important factor associated with screen time is smoking habit, with smokers spending more time watching TV 25 . Conversely, smokers appear to spend more time in front of a screen with smoking cessation influencing this association by reducing screen time 26 .…”
Section: Screen Time For Work (First Row) or Entertainment (Second Ro...mentioning
confidence: 99%
“…Respecto a los hábitos alimentarios, los niños que consumían mayor cantidad de verduras dedicaban menos tiempo a la TV (p<0,05); mientras que el mayor consumo de azúcar se concentró en niños que pasaban mayor cantidad de horas viendo TV (p<0,05), hechos que han sido reportado por otros estudios (18,22,27), especialmente en varones, quienes según nuestros resultados presentaron una mayor diferencia significativa, similar a lo planteado en un artículo publicado el año 2010 basado en niños europeos, el cual reveló que ver TV y el sexo masculino son importantes predictores para la comida rápida, bebidas azucaradas y peso corporal (26). Los análisis de contenido han demostrado que la alimentación es la categoría que con más frecuencia se anuncia en la TV de los niños, centrándose en productos muy dulces; más recientemente las promociones de comida rápida ha ido creciendo (27), en donde el tiempo de TV como actividad sedentaria, y su publicidad, se postula como un incentivador para el consumo de azúcar y grasas (6,28).…”
Section: Tablaunclassified
“…Estudios previos a la situación de pandemia por COVID-19, han reportado que los estudiantes universitarios chilenos tienden a mantener conductas sedentarias y un bajo nivel de actividad física 6 , asociado a una mayor probabilidad de desarrollar enfermedades como obesidad, diabetes e hipertensión 6,7 , y a una menor percepción de la calidad de vida relacionada con la salud 8 . Esto se suma a que una mayor dedicación a horas de estudio y una alta exposición al uso de pantallas (computador y/o smartphone) lo que promueve la adquisición de estilos de vida no saludables en esta población 6,9,10 . En la actualidad, debido a las restricciones de distanciamiento social impuestas por los gobiernos debido a la pandemia por COVID-19, muchos jóvenes universitarios han debido reemplazar las actividades académicas presenciales por actividades académicas online.…”
unclassified